EFEKTIFITAS KONSELING KELOMPOK COGNITIVE BEHAVIOR THERAPY SEBAGAI STRATEGI INTERVENSI KESULITAN BELAJAR SISWA SMPN 3 TALANG - Azmy, Mohammad Firchan; Ayuningtyas, Ira Palupi Inayah; Atmaja, Jati Rinakri (Universitas Muria Kudus, 2024)
This research was motivated by problems often experienced by students as shown by declining academic achievement. The purpose of this study was to determine the level of student learning difficulty and the effectiveness of group counseling with cognitive behavior therapy in reducing learning difficulties in grade IX SMPN 3 Talang. The method used is experimental research with a pretest posttest one group pretest design. The results showed that (1) the level of learning difficulty was quite high; (2) group counseling with cognitive behavior therapy can reduce learning difficulties such as by decreasing pretest and posttest scores by 43.88 to 26.22; (3) Group counseling with cognitive behavior therapy is effective as an intervention strategy for learning difficulties shown by the results of paired sample t-tests showing significant changes.